Antecedents of BIM Training Effectiveness amongst AEC Firms in New Zealand - Rotimi, James; Arasanmi, C.; Rotimi, Funmi; Ramanayaka, Chamil Erik; Komolafe, A. (World Scientific Publishing Company, 2019)
Building information modelling (BIM) is radically changing the face of construction project management. BIM adoption is significant in alleviating the attendant problems of poor detailing, communication and coordination because of its inherent integrative technology. Several BIM training initiatives have occurred within the construction industry in New Zealand, but the knowledge base on the success of these training initiatives is at its infancy. Furthermore, there is a dearth of research on how acquired knowledge and skills in BIM implementation have been transferred to other end users post training. This chapter seeks to understand BIM knowledge transfer mechanisms among AEC members. The chapter proposes a model of the enablers of BIM knowledge transfer and effective utilization of skills and knowledge in a BIM environment, and presents the psychometric analysis of the research instrument in this exploratory phase of the study.